Shameful Flight : The Last Years of the British Empire in India - Wolpert, Stanley (Karachi, Pakistan Oxford University Press, 2016)
Ranging from the fall of Singapore in 1942 to the assassination of Mahatma Gandhi in 1948, this text provides a vivid behind-the-scenes look at Britain's decision to divest itself from the crown jewel of its empire. Wolpert, a leading authority on Indian history, paints memorable portraits of all the key participants.
Include Index, Bibliography, Notes and Illustration
Keywords: India -- British -- Partition of India (1947)